MicroRNA-122-3p plays as the target of long non-coding RNA LINC00665 in repressing the progress of arthritis. Issue 5 (2nd May 2022) - Wang, Zhiyan; Tian, Qijun; Tian, Yumei; Zheng, Zhonghua
ABSTRACT: MicroRNAs (miRNAs) play important roles in many diseases, including rheumatoid arthritis (RA). However, the mechanisms underlying the effects of miR-122-3p-3p on RA are not distinct and require further investigation. Patients with RA and healthy controls were recruited to analyze the miR-122-3p levels. The MH7A cells were stimulated with interleukin (IL)-1β to mimic the local inflammation of RA. Cell Counting Kit-8 (CCK-8) and flow cytometry were performed to measure the viability and apoptosis of MH7A cells. Diana tools and TargetScan were used to predict the target relationships. Luciferase reporter assay was used to validate the target relationship. miR-122-3p is downregulated in RA patients and IL-1β-stimulated MH7A cells. miR-122-3p suppresses MH7A cell viability and promotes MH7A cell apoptosis. miR-122-3p targets LINC00665. LINC00665 eliminates the inhibitory effect of miR-122-3p on IL-1β-stimulated MH7A cells. Eukaryotic translation initiation factor 2 alpha kinase 1 (EIF2AK1) targets miR-122-3p. In addition, EIF2AK1 is highly expressed in patients with RA. In addition, EIF2AK1 activates the mTOR signaling pathway. miR-122-3p represses RA progression by reducing cell viability and increasing synoviocyte apoptosis. Graphical Abstract: uf0001